Identification of the active region responsible for the anti-thrombotic activity of anopheline anti-platelet protein from a malaria vector mosquito. (June 2013) - Hayashi, Hideki; Kyushiki, Hiroyuki; Nagano, Keisuke; Sudo, Toshiki; Iyori, Mitsuhiro; Matsuoka, Hiroyuki; Yoshida, Shigeto
<x xml:space="preserve">Abstract</x> We previously identified an anti-platelet protein, anopheline anti-platelet protein (AAPP), from the salivary gland of female Anopheles stephensi (a mosquito vector of human malaria). AAPP specifically blocks platelet adhesion to collagen by binding directly to collagen and subsequently causing platelet aggregation. The aim of this study was to identify the active region of AAPP responsible for the anti-thrombotic activity because we hypothesized that AAPP could be used as a candidate anti-platelet drug. Various truncated forms of AAPP were produced using an Escherichia coli expression system. Each protein was examined for binding activities to soluble/fibrillar collagen and anti-thrombotic activity using a plate assay and platelet/whole blood aggregation study, respectively. Among the truncated forms examined, only a protein encoded by exon 3–4 (rAAPPex3–4) effectively bound to soluble/fibrillar collagen in a concentration-dependent and saturable manner. The EC50 values of full-length AAPP and rAAPPex3–4 for soluble collagen binding were 35 nM and 36 nM, respectively. In contrast to soluble collagen, there was a difference in binding affinity to fibrillar collagen between full-length AAPP and rAAPPex3–4, with EC50 values of 31 nM and 51 nM, respectively. rAAPPex3–4 also inhibited aggregation of platelets/whole blood, and the IC50 values of full-length AAPP and rAAPPex3–4 for platelet aggregation were 35 nM and 93 nM, respectively. These results indicated that the essential moiety of AAPP for collagen binding and anti-thrombotic activity was in the region encoded by exon 3–4, which is highly conserved among the counterpart regions of other mosquito species.